DIAGNOSTICS OF HEMOSTASIS DISORDERS IN INFANTS - A. L. Mishchenko; N. M. Khamani; N. S. Stuleva (Акушерство, гинекология и репродукция)
This clinical lecture is dedicated to the diagnostic approaches of blood coagulation disorders in newborns. The work presents a clinical substantiation of different diagnostic methods of hemostasis disorders with description of routine standard methods of research and special techniques.